Pengaruh Likuiditas, Leverage, Profitabilitas, dan Good Corporate Governance terhadap Risk Management Disclosure - Reza Rosiani; Fiola Finomia Honesty (Universitas Negeri Padang, 2023)
The objective of this research is to investigate the impact of liquidity, leverage, profitability, and good corporate governance as proxied by independent commissioners, and audit committees on the disclosure of risk management. The data utilized in this study comprises secondary data derived from the annual reports of property and real estate firms listed on the Indonesian stock exchange from 2018 to 2021. The sample was selected using purposive sampling technique, resulting in a total of 28 companies included in the sample. Multiple linear regression analysis was employed as the analytical model in this research. The findings indicate that the audit committee exhibits a positive and statistically significant influence on risk management disclosure. Conversely, the independent commissioner demonstrates a negative and statistically significant impact on risk management disclosure. Moreover, the study reveals that liquidity, leverage, and profitability do not have a significant effect on risk management disclosure.